Benign Hand Tumors (Part I): Cartilaginous and Bone Tumors. (March 2022) - Yue, Kai-Lou C.; Lans, Jonathan; Castelein, René M.; Suster, David I.; Nielsen, G. Petur; Chen, Neal C.; Lozano-CalderÓn, Santiago A.
Background: Benign tumors of the hand present in a wide array of histological subtypes and compose most of the bony tissue tumors in the hand. This study evaluates the characteristics and treatment of benign bone tumors in light of one institution's experience.Methods: Histologically confirmed benign tumors of the hand were retrospectively identified using International Classification of Diseases codes from 1992 to 2015. A medical chart review was conducted to collect patient characteristics and tumor epidemiology and treatment.Results: A total of 155 benign bone tumors were identified. The median age of patients at the time of surgery was 39.9 ± 12.8 years. All bone tumors were located in the digits, and most were treated by intralesional curettage (n = 118, 76%). Pathologic fractures occurred in 79 bone tumors (51%).Conclusion: Enchondromas (n = 118, 76%) were the most common bone tumor in this series, whereas giant cell tumors were the most destructive and also had the highest recurrence rate (40%). Awareness of tumor features may help physicians with diagnosis, and awareness of recurrence rates is important when counseling patients.